HABITAT BEKANTAN (Nasalis larvatus Wurmb) DI DALAM DAN SEKITAR AREAL IUPHHK-HT PT. BINA SILVA NUSA KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Widiastuti, Febriani; Erianto, .; Rifanjani, Slamet (Universitas Tanjungpura, 2017)
Proboscis monkey (Nasalis larvatus Wurmb) is a primate that included in the family of Cercopithecidae. Proboscis monkeys are rare and endemic animals of Borneo, they are protected species and classified in Appendix I of CITES with the conservation status are endangered by the IUCN. The area of IUPHHK-HT PT. Bina Silva Nusa and its surroundings are the habitat of the proboscis with the mean mangrove forests and peat bogs. The purposes of this research are to obtain data and information of the habitat of proboscis monkeys in the area of IUPHHK-HT in the form of tree species, feed trees, sleeping trees, water, temperature and humidity. The data collecting was limited on the location that discovers the groups of proboscis monkeys and the sleeping place of proboscis. The research method was using terraced path to investigate the species of trees and undergrowth as the habitat and the potential feed source tree and the tree of sleep. The Habitat of proboscis monkeys on the three type of forest relatively had good vegetation structure. There are 21 species of trees and undergrowth was found as a food source and also used as a sleeping tree. The preferred tree species are the white mangrove (rhizophora apiculata), dungun (Heritiera globosa), ubah (Syzygium spp), ketiau (Ganua motleyana) and undergrowth piai lasa (Acrostichum speciosum). Water was known the salinity average of 15,5 o/oo - 22,5 o/oo with mean of pH of 3,75 – 5,5. Results of research on air temperature of habitat of proboscis monkey ranged between 25,8 ° C to 33 °C and the humidity ranged from 71,67% to 81, 33%. Keywords: Feed Trees, Habitat of Proboscis Monkey, PT. Bina Silva Nusa, Sleeping Trees